2021
DOI: 10.1111/ijfs.15307
|View full text |Cite
|
Sign up to set email alerts
|

Application of biopreservatives in meat preservation: a review

Abstract: As a highly perishable food, raw meat, if not preserved, will spoil due to the altered metabolism, microbial activity and external factors during storage. Biopreservatives, as a new type of preservatives, are characterised by nontoxicity, extensive source and good application prospects in the raw meat. This review discusses the factors responsible for the spoilage of raw meat, recaps the spoilage bacteria in the raw meat and summarises the major antibacterial mechanism of various biopreservatives. Moreover, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 106 publications
(175 reference statements)
0
5
0
Order By: Relevance
“…One of the most common causes of meat spoilage during storage, in addition to microbial factors, is the lipid oxidation of meat [ 51 ]. This can be caused by lipid hydrolysis or the oxidation of polyunsaturated fatty acids [ 4 ]. The level of lipid oxidation is expressed as the amount of MDA, the main stable oxidation product of polyunsaturated fatty acids [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common causes of meat spoilage during storage, in addition to microbial factors, is the lipid oxidation of meat [ 51 ]. This can be caused by lipid hydrolysis or the oxidation of polyunsaturated fatty acids [ 4 ]. The level of lipid oxidation is expressed as the amount of MDA, the main stable oxidation product of polyunsaturated fatty acids [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, many microorganisms have developed resistance to the action of the permissible concentrations of synthetic preservatives [ 3 ]. For these reasons, there is a justified demand from consumers, as well as science and the meat industry, for screening and application of natural, safe and effective preservatives [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) are generally recognized as safe (GRAS) by the Food Drug Administration (FDA) and have a positive effect on the preservation of agricultural products [ 7 , 8 , 9 ], which are applied to inhibit the growth of spoilage microorganisms, delay peel discoloration, regulate the metabolism of reactive oxygen species, and decompose the browning substrates. It was found that Lactobacillus delbrueckii screened from fermented yak milk effectively extended the shelf life of strawberries by inhibiting the growth of spoilage microorganisms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…chitosan) and microbial source preservatives (e.g. nisin and lysozyme) (Hussain et al ., 2021; Ren et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%